2014
DOI: 10.17338/trainology.3.2_41
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise intensity on perceived exertionduring multiple sets of bench press to volitional failure

Abstract: Objectives:The purpose of this study was to investigate the effects of intensity on rating of perceived exertion (RPE) during multiple sets to volitional failure in bench press exercise. Design and Methods: Thirteen moderately resistance trained men performed 2 experimental sessions in random order: 3 sets to failure in bench press with 1 minute rest at an intensity of 50% and 70% of 1 repetition maximum (1RM). RPE was measured using the OMNI scale after each set. Readiness to Invest in Physical (RTIPE) and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Such condition is related to a momentary increase in difficulty of execution and exercise intensity, as well as, possibly, to a physiological increase in lactate, phosphocreatine depletion and decreased blood pH, which can induce a greater RPE during strength exercises 5,11 . As a result of these physiological changes, there may be a reduction in the number of repetitions throughout the sets 16 , which was also verified in our study, thus corroborating our initial hypothesis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Such condition is related to a momentary increase in difficulty of execution and exercise intensity, as well as, possibly, to a physiological increase in lactate, phosphocreatine depletion and decreased blood pH, which can induce a greater RPE during strength exercises 5,11 . As a result of these physiological changes, there may be a reduction in the number of repetitions throughout the sets 16 , which was also verified in our study, thus corroborating our initial hypothesis.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, when bench press was executed until concentric failure at 50% or 70% of 1RM, no difference in RPE was observed, despite the greater total weight lifted in the 50% 1RM condition16. In a study conducted by Silva et al 16 , cadence was free, i.e., not controlled by the researchers. In their turn, while investigating the influence of cadence on RPE, Diniz et al 12 showed that the participants who performed the experimental protocol at a slow movement velocity (2 seconds of concentric action for 4 seconds of eccentric action) presented a higher RPE, both per set and total, and a lower volume of total In the present study, the participants who performed the protocols at moderate (2020) and free movement velocities presented a lower RPE throughout the sets, as well as and higher volumes of repetition, corroborating the findings of Day et al 16 , according to which the group that executed the protocol with less intensity performed a greater number of repetitions and presented a lower RPE.…”
Section: Discussionmentioning
confidence: 99%
“…As we have recently noted in several papers ( Steele, 2014 ; Steele et al, 2017b ; Steele et al, 2017a ), and as have others, differentiation between perceptions of effort and discomfort are important ( Abbiss et al, 2015 ; Marcora, 2009 ; Smirnaul, 2012 ) particularly within RT ( Steele, 2014 ; Steele et al, 2017b ). In studies using traditional rating of perceived exertion scales higher ratings are given, despite conditions being controlled by supposedly training to MF, with lower loads for lower body exercise ( Shimano et al, 2006 ), as set volume increases ( Silva et al, 2014 ), with increased volume-load ( Pritchett et al, 2009 ), and with increased work rate ( Hiscock et al, 2016 ; Hiscock, Dawson & Peeling, 2015 ) supporting that participants may have expressed their feelings of increasing discomfort ( Steele, 2014 ; Steele et al, 2017b ; Steele et al, 2017a ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we can only assume that the participants were unclear as to how to report their perception of effort. Increasing ratings of effort were, however, given with conditions known anecdotally to produce greater acute discomfort, such as lower load lower body exercise, as set volumes increased, with increased work volume, and with increased work rate . This suggests participants were more likely to express their feelings of increasing discomfort .…”
Section: Definitions Of Set Endpointsmentioning
confidence: 98%
“…Differentiation between perceptions of effort and discomfort have been highlighted recently as important, particularly in RT, for good reason. A number of studies measuring rating of perceived exertion (RPE) using a Borg CR10 scale (where a value of 10 indicates maximal effort) reported that participants exercised to MF and received verbal encouragement to ensure adequate motivation and effort. In this case, each trial, irrespective of exercise, load, or training status, should have resulted in a maximal value for effort, because people were exercising to MF.…”
Section: Definitions Of Set Endpointsmentioning
confidence: 99%